Overexpression of human NR2B receptor subunit in LMAN causes stuttering and song sequence changes in adult zebra finches - Mukta Chakraborty (Nature Portfolio, 2017)
Abstract Zebra finches (Taeniopygia guttata) learn to produce songs in a manner reminiscent of spoken language development in humans. One candidate gene implicated in influencing learning is the N-methyl-D-aspartate (NMDA) subtype 2B glutamate receptor (NR2B). Consistent with this idea, NR2B levels are high in the song learning nucleus LMAN (lateral magnocellular nucleus of the anterior nidopallium) during juvenile vocal learning, and decreases to low levels in adults after learning is complete and the song becomes more stereotyped. To test for the role of NR2B in generating song plasticity, we manipulated NR2B expression in LMAN of adult male zebra finches by increasing its protein levels to those found in juvenile birds, using a lentivirus containing the full-length coding sequence of the human NR2B subunit. We found that increased NR2B expression in adult LMAN induced increases in song sequence diversity and slower song tempo more similar to juvenile songs, but also increased syllable repetitions similar to stuttering. We did not observe these effects in control birds with overexpression of NR2B outside of LMAN or with the green fluorescent protein (GFP) in LMAN. Our results suggest that low NR2B subunit expression in adult LMAN is important in conserving features of stereotyped adult courtship song.